Exploring effective secondary schools in challenging contexts: a study in two Chilean regions - Balbontín Alvarado, Roxana P. (2012)
School effectiveness in areas of social deprivation is a fundamental issue for every society, because it is related to social justice, equity and development, which are important matters for every developed or developing country. Social justice in education means that any student, whatever their social background, has equal access and opportunities to receive an education of quality.